Incisional hernia by liver cysts. Issue 11 (10th November 2022) - Giuffrè, Mauro; Budel, Martina; Martingano, Paola; Crocè, Lory Saveria
Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most commonly inherited kidney disease and is associated with cystic manifestation in the liver. Patients with ADPKD are at higher risk for hernias, here we present an image of an incisional hernia full of multiple liver cysts. Abstract : A rare case of incisional hernia full of liver cysts forming a subcutaneous mass of 14 × 14 × 4 cm.